DESIGNING A READING TEACHING MATERIAL BASED ON THE STUDENTS’ WEAKNESS POINTS IN ANSWERING UN READING TESTS AT SMA EXCELLENT AL-YASINI IN ACADEMIC YEAR 2014/2015 - Hidayati, Putri Nurul (Educate, 2015)
The senior high school students often had difficulty understanding and answering UN Reading questions so that they had English UN scores less than 4,00. This research is aimed at designing a reading teaching material for the twelfth grade students of SMA Excellent Al-Yasini Kraton Pasuruan. The teaching material was based on the students’ weakness points in answering UN reading questions. The method used of this research was quantitative analysis. Meanwhile, the sampling was cluster random consisting of 20 students. The data were collected through test and analyzed by using percentage calculation. The findings of this research as follows, the students mainly had difficulty on three types of questions in explanation text: word meaning (100%), unstated information (90%), and main idea (80%), in discussion text, it was identified that the students had problem dealing unstated information (85%) and detailed information (75%), the most problematic question for the students in news item was detailed information (95%) and in exposition text, detailed information (85%) was also the students’ difficulty. Based on the findings, it can be concluded that the teaching material developed consisted of the materials that were in accordance with the students’ proficiency level as shown by the results of the research Key word: UN, student’s needs, teaching material